Eosinophilic colitis presenting with lower gastrointestinal bleeding: An uncommon entity with a rare presentation - Ayşe Kefeli; Abdullah Özgür Yeniova; Sebahat Başyiğit; Nedim Güneş (Turkish Journal of Gastroenterology, 2019)
-